The Docker video collection - Hykes, Solomon (O'Reilly Media, 2016)
"Containers have introduced a sea change into how development and ops teams are working together and deploying their product. Starting with a thorough introduction the collection also includes in depth content on security and performance as well as about how containers have brought about that new collaboration across engineering teams."--Resource description page.
Title from resource description page (viewed July 28, 2016). - Selected videos from the O'Reilly OSCON Open Source Convention: May 16-19, 2016, Austin, TX
Keywords: Computer software -- Development; Electronic data processing -- Distributed processing; Traitement réparti; Computer software; Development; Electronic data processing; Distributed processing; Electronic videos